Development and validation of the COugh Assessment Test (COAT). Issue 6 (25th January 2019) - Koo, Hyeon‐Kyoung; Jeong, Ina; Kim, Joo‐Hee; Kim, Sung‐Kyoung; Shin, Jong‐Wook; Park, So Young; Rhee, Chin Kook; Choi, Eun Young; Moon, Ji‐Yong; Kim, Yee Hyung; Lee, Hyun; Kang, Hye Seon; et al.
ABSTRACT: Background and objective: A cough‐specific quality‐of‐life questionnaire is recommended to assess the impact of cough; however, a simple instrument to quantify cough is required for everyday clinical practice. This study was aimed to develop a short patient‐completed questionnaire (COugh Assessment Test, COAT). Methods: The COAT was developed and validated by comparison with the Korean version of Leicester Cough Questionnaire (K‐LCQ) and cough numeric rating scale (NRS, 0–10, 11‐point scale) for chronic cough patients. Results: Item selection identified five items regarding cough frequency, daily activity, sleep disturbance, fatigue and cough hypersensitivity (0–4 scaling of items, 0–20 score range) through reliability test cohort ( n = 78). Test–retest reliability was strong (intra‐class correlation coefficient = 0.88). The final COAT was compared with K‐LCQ and cough NRS in a validation cohort ( n = 323). In Rasch analysis, COAT fitted well to a unidimensional model. Pearson correlations of COAT versus K‐LCQ (i) before treatment, (ii) after treatment; COAT versus cough NRS (iii) before treatment, (iv) after treatment; (v) delta‐COAT versus delta‐cough NRS, (vi) delta‐COAT versus delta‐K‐LCQ were (i) −0.71, (ii) −0.81, (iii) 0.69, (iv) 0.82, (v) −0.66 and (vi) 0.72, respectively. Conclusion: The COAT is a useful, simple questionnaire for assessing and monitoring cough. Abstract : The COugh Assessment Test (COAT) is a simple assessment that has good repeatability, reliability and validity, with clear discriminative properties. The COAT might serve as a useful parameter for the evaluation of chronic cough in clinic and research settings. See related Editorial